Time Trends in Hypertension and Diabetes Prevalence by Body Mass Index Categories in Brazilian Adults from 2006 to 2023 - De Moraes-Ferrari, G (John Wiley and Sons Inc, 2024)
Aim: The prevalence of diabetes and hypertension according to body mass index (BMI) status in Brazilian adults has not been described yet. Herein, we aimed to identify the time trends in hypertension and diabetes, individually and combined (multimorbidity), by BMI in Brazilian adults. Methods: In this time series cross-sectional study, we retrieved self-reported data from 806 169 adults between 2006 and 2023, using the Surveillance System of Risk and Protective Factors from Chronic Diseases by Telephone Survey (Vigitel). Weight and height were used to classify participants into normal/underweight (<25 kg/m2), pre-obesity (25 to 29.9 kg/m2), and obesity (≥ 30 kg/m2). We calculated the prevalence of medical diagnoses of hypertension and diabetes, individually and combined, by BMI categories, and by sociodemographic characteristics (sex, age group, educational attainment) for participants with obesity. We performed Prais-Winsten linear regression models to identify temporal trends. Results: The prevalence of hypertension and diabetes increased between 2006 and 2023. Among adults with obesity, we observed a slight decrease in the prevalence of hypertension (from 44.5% in 2006 to 41.7% in 2023) and the prevalence of either hypertension or diabetes (47.1% to 45.5%); an increase in the prevalence of diabetes (12.8% to 15.13) and both conditions combined (10.2% to 11.2%). Participants with obesity had more than twice the prevalence of hypertension and diabetes compared with those who were normal/underweight. We observed a differential time trend by sex, age group, and educational attainment. Conclusion: Our findings indicate the need for differentiated approaches for interventions for hypertension and diabetes, considering variations over time by sociodemographic characteristics. © 2024 John Wiley & Sons Ltd.